Kajian Pembelian Impulsif Lewat Toko Online Pada Masyarakat Perkotaan - Agus Salim, SE., MBA., MM (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2016)
Along with many shops have sprung up online and the use of smart phones and computers is increasingly widespread encourage urban communities tend to shop via the Internet. People often assume that an addiction to anything is the thing that will always have a negative impact, but marketers assume that people addicted to this as an opportunity to market their products. In this situation, the behavior of consumers who have hedonic properties can be used to market its products by leveraging the Internet. The object of this research is a promotional program, hedonic motivation and impulse purchases online shop customers. Subjects in this study is the urban communities around Jabodetabek ever made a purchase at the online store. There is no positive influence between variable signifikat and promotional programs with impulsive purchases. There is no signifikat and positive influence between variable motivas hedonists with impulsive purchases.